The analysis of non‐stress effects on historical stone bridge structures (monitoring, theoretical analysis, maintenance) - Witzany, Jiří; Zigler, Radek (Journal of Civil Engineering and Management, 2007)
Due to non‐stress cyclic effects of temperature and moisture, stone bridge structures are subjected to deformations, a gradual growth of permanent deformations, crack development and subsequent disintegration of the stone masonry of bridge vaults. A theoretical analysis of the stress‐state and deformations of the stone bridge structure caused by non‐stress effects and the in‐situ monitoring of deformation changes of the breast walls and the bridge vaults of the historic structure of Charles Bridge (from the mid‐14th century) manifested a response and a growth in permanent deformations and disintegration of the stone bridge structure due to the effects of temperature and moisture. The behaviour of the bridge structure is significantly affected by the interaction of the vault bridge structure with the bridge body filler when exposed to the above‐mentioned non‐stress effects. Special attention must be paid to the spacing effect of filling layers on the stone bridge structure. When repairing historical stone bridge structures, the rehabilitation methods commonly used increase the total rigidity of the stone bridge structure and thus its sensitivity to non‐stress effects caused by changes in temperature.Klimatinių poveikių įtakos mūrinio istorinio tilto konstrukcijoms analizė (priežiūra, teorinė analizė, remontas)Santrauka. Cikliniai temperatūros ir drėgmės poveikiai mūrinių tiltų konstrukcijose sukelia papildomas deformacijas, laipsnišką ilgalaikių deformacijų augimą, plyšių vystymąsi. Šie veiksniai lemia tilto skliautų mūro skilimą. Padaryta XIV amžiuje statyto Karlo mūrinio tilto Prahoje klimatinių poveikių sukelto įtempių ir deformacijų būvio analizė. Atlikti šio tilto antstato ir skliautų deformacijų natūriniai stebėjimai. Teoriniai ir eksperimentiniai tyrimai parodė, kad temperatūros ir drėgmės pokyčiai turi didelę įtaką tilto konstrukcijų įtempių ir deformacijų būviui. Klimatinių poveikių įtaka tilto elgsenai labai priklauso ir nuo skliautų, ir antstato užpildymo sąveikos. Itin daug dėmesio reikia skirti antstato užpildymo sluoksnių storiui. Atlikus istorinių mūrinių tiltų konstrukcijų remontą standartinėmis technologijomis, bendrasis tilto konstrukcijos standumas padidėja, drauge jis tampa jautresnis klimatiniams temperatūros ir drėgmės poveikiams.Reikšminiai žodžiai: cikliniai poveikiai, ilgalaikės deformacijos, skilimas, klimatiniai poveikiai, sąveika, drėgmė.First Published Online: 14 Oct 2010